(3egPH GdhUhd Edi Yde GdCUhds - (3eMeO egOj Hf GdMSf Hf CMeO GdMSjfj GdbRhjfj GdfLaj,J (B1300 (3g` s ((3CMeO Hf GdTjN MSf s)
(3ChdgG (B:s
(3Gdbhd HMLjI GdGSJUMGH QHeG dGjbhdhf eKd hgfG eY Gf GdESJUMGH s
(3BNQgG (B:s
(3HeG UOQ ef gahGJ GdCbdGe heRGQ GbOGe GdChgGe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B114s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis